An empire divided : religion, republicanism, and the making of French colonialism, 1880-1914 - Daughton, J. P. (James Patrick) (Oxford University Press, 2006)
Between 1880 and 1914, tens of thousands of men and women left France for distant religious missions, driven by the desire to spread the word of Jesus Christ, combat Satan, and convert the world's pagans to Catholicism. But they were not the only ones with eyes fixed on foreign shores. Just as the Catholic missionary movement reached its apex, the young, staunchly secular Third Republic launched the most aggressive campaign of colonial expansion in French history. Missionaries and republicans abroad knew they had much to gain from working together, but their starkly different motivations regul.